Impact of Cigarette Access and Pocket Money on Adolescent Smoking in Rural and Urban Padang City - Melisa Yenti; Arinil Haq; Anggela Pradiva Putri; Hanifa Eka Putri; Shabrina Erila; Dela Desmita Sari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Referring to the results of the Indonesian Health Survey, it was reported that the largest group of smokers were adolescents aged 15-19 years (56.5%) in 2023. There was an increase in the percentage of novice smokers in Padang City in 2024 which reached 49%. So it is necessary to carry out appropriate handling. One of them is by conducting this study to determine the effect of cigarette access and pocket money on adolescent smoking behaviour in urban and rural areas. Method: This quantitative study involved a comparative cross-sectional design conducted in Padang City. Involving adolescents aged 16-19 years in rural and urban areas of Padang City conducted accross April-June 2024. A total of 106 adolescents enrolled as samples and data were collected through filling out questionnaires. Ethical approval was obtained from the research ethics committee team of the Faculty of Public Health, Andalas University, and approval was given by issuing a permit letter. Results: The primary outcome of the study suggest that ease of access to smoking has a strong influence in determining the difference of adolescent smoking behaviour in rural and urban areas Sig= 0.002 (p<0.005). Rural areas also produce more smokers than urban areas (67.9%) with a significant relationship to adolescent smoking behaviour (p= 0.002). Conclusion: In conclusion, our study contributes to the prevention of adolescent smoking behavior that parents and communities can implement and suggests policies that can restrict it within the scope of the social environment. Future studies should address differences in adolescent smoking behavior based on the involvement of health workers. And using the mixed method so that the data produced can be more representative which ultimately advances knowledge in the field of international health.